2015
DOI: 10.1111/jen.12209
|View full text |Cite
|
Sign up to set email alerts
|

Fitness costs of resistance to Cry3Bb1 maize by western corn rootworm

Abstract: Crops producing toxins derived from the bacterium Bacillus thuringiensis (Bt) are widely planted to manage insect pests including western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), which is a significant pest of maize in the United States and Europe. However, the widespread use of Bt maize places intense selection pressure on pest populations to evolve resistance, and field-evolved resistance to Bt maize by western corn rootworm has been documented in the United States. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 43 publications
3
32
2
Order By: Relevance
“…Other studies have shown that larvae feeding only on Cry3Bb1-expressing plants develop into smaller adults. 12,13,27 It is possible that size similarities in our study resulted from larvae moving between refuge and Bt plants [28][29][30] or that there were no effects on size from Cry toxin feeding, as observed in some WCR populations. 11,29,31 Emergence timing may also influence mate selection.…”
Section: Discussionmentioning
confidence: 85%
“…Other studies have shown that larvae feeding only on Cry3Bb1-expressing plants develop into smaller adults. 12,13,27 It is possible that size similarities in our study resulted from larvae moving between refuge and Bt plants [28][29][30] or that there were no effects on size from Cry toxin feeding, as observed in some WCR populations. 11,29,31 Emergence timing may also influence mate selection.…”
Section: Discussionmentioning
confidence: 85%
“…; Hoffmann et al. ). Hence, more studies are needed to characterize field‐evolved WCR‐resistant populations (Hoffmann et al.…”
Section: Discussionmentioning
confidence: 98%
“…Hence, more studies are needed to characterize field‐evolved WCR‐resistant populations (Hoffmann et al. ; Ingber and Gassmann ), and especially, studies were conducted to evaluate the current spatial variability in susceptibility of populations to Bt traits to determine the type of environment current and future technologies will be deployed in agroecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with Cry3Bb1-resistant laboratory strains of D. virgifera feeding on non-transgenic maize showed either a fitness benefit [42] or costs and benefits in different fitness components [43]. In experiments with the Bar-le-Duc-resistant strain of C. tremula studied by Wenes et al [27], the frequency of the recessive resistant allele declined from 0.5 to 0.179 over five generations of rearing on non-Bt poplar, indicating a fitness cost of resistance.…”
Section: Discussionmentioning
confidence: 99%